Analisis Kesulitan Belajar Matematika dalam Menyelesaikan Soal Cerita Siswa Kelas V SDN Poris Pelawad 6 Kota Tangerang - Asti Octavia; Erdhita Oktrifianty; Yoyoh Fathurrohmah (Jurnal Halaqah, 2021)
This study aims to determine whether students have difficulty in learning mathematics in story problems with the volume of cubes and blocks for class V SDN Poris Pelawad 6 Tangerang City, the research method used is qualitative and the sample is taken randomly, using a sample of 7 students and using descriptive qualitative methods and data collection techniques used were observation, interviews, documentation and tests, the most errors were errors in process skills as much as 52.94% while the least errors in understanding the questions were 15.69%.